Gambling with the family silver: Household consumption and saving responses to fiscal uncertainty - Oddmund Berg (Statistics Norway, Research Department, 2019)
In the early 2000s, eight Norwegian energy producing municipalities sold up to ten years of future electricity earnings and let two brokers from Terra Securities make investments on their behalf. In the wake of the 2007 credit crash the municipalities lost up to 80 percent of their assets. This paper uses a difference in difference analysis to show that this tightening of the local government budget, and accompanying uncertainty about future economic outcomes, led to a reduction in private consumption of around 2 percent in 2008. I show that the response is driven by households who are the largest recipients of public services - the young and the elderly. The reduction in consumption is a result of households saving more, and not a direct consequence of changes in their disposable income. I also find that households in the affected municipalities rebalance their portfolios to holding a lower share of risky assets. The results are interpreted as households holding back consumption, and reallocating towards safer assets, until uncertainty regarding fiscal outcomes is resolved.
Keywords: D12; E21; E65; H31; 330; Fiscal uncertainty; consumption and saving; panel data; natural experiment